Social and Environmental Responsibility: Treatment and Final Disposal of Used Tires in The City of Machala - Espinoza Enríquez, Leonardo (2020)
The present bibliographic and documentary work is based on analyzing alternatives such as: a management model of social and environmental responsibility for the treatment of used tires in the city of Machala, El Oro province, Ecuador, for which data were obtained statistics from public bodies and official pages. In addition, visits were made to sites where alternatives are being implemented to reduce the problem of disused tires when they end their useful life and thus take advantage of them as raw material. This has allowed to know the problems present in the city, through the relationship between the variables: population growth and the number of cars registered annually in this city and the impact of this special waste on the natural environment and human health. A social and environmental responsibility model is designed based on the ISO 26000 standard through the establishment of a guideline for companies that are in charge of giving added value to used tires. It is concluded that the use of efficient alternatives to generate an added value from used tires is considered as a model of social and environmental responsibility that will help reduce the problems caused by used tires after their useful life.